2013
DOI: 10.1021/jp312822t
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Bonding in MPb5 (M = Cu, Ag, and Au): A Combined Investigation by Theoretical Calculations and Photoelectron Imaging Spectroscopy

Abstract: Bimetallic clusters of MPb 5− (M = Cu, Ag, and Au) have been studied using density functional theory and photoelectron imaging spectroscopy. These anionic clusters and their neutrals were determined to be a Pb 5 trigonal bipyramid with the coinage metal atom on its triangular facet. This structure of each MPb 5 − or MPb 5 was found to be more than 0.5 eV lower than other structural candidates and that of each

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Among others, Tang et al found that lead clusters react with alkene, acetone and benzene, enabling the activation of the C–C and C–H bonds through different reaction pathways. Also, bimetallic clusters of MPb 5 – (M = Cu, Ag, and Au) have been studied, utilizing photoelectron spectroscopy, shedding light on relativistic electronic effects in clusters containing heavy atoms . Besides, the transition from covalent to metallic bonding in the Pb n clusters has likewise attracted interest. , It was even proposed that Pb particles could be solid state for small clusters while liquid for larger ones under condensation of lead atoms in cold He gas. , In spite of the existing literature on this subject, it is fair to say that the size-dependent properties of Pb n + clusters and structural implications for their chemical properties are still open questions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among others, Tang et al found that lead clusters react with alkene, acetone and benzene, enabling the activation of the C–C and C–H bonds through different reaction pathways. Also, bimetallic clusters of MPb 5 – (M = Cu, Ag, and Au) have been studied, utilizing photoelectron spectroscopy, shedding light on relativistic electronic effects in clusters containing heavy atoms . Besides, the transition from covalent to metallic bonding in the Pb n clusters has likewise attracted interest. , It was even proposed that Pb particles could be solid state for small clusters while liquid for larger ones under condensation of lead atoms in cold He gas. , In spite of the existing literature on this subject, it is fair to say that the size-dependent properties of Pb n + clusters and structural implications for their chemical properties are still open questions.…”
Section: Introductionmentioning
confidence: 99%
“…Also, bimetallic clusters of MPb 5 − (M = Cu, Ag, and Au) have been studied, utilizing photoelectron spectroscopy, shedding light on relativistic electronic effects in clusters containing heavy atoms. 45 Besides, the transition from covalent to metallic bonding in the Pb n clusters has likewise attracted interest. 34,46 It was even proposed that Pb particles could be solid state for small clusters while liquid for larger ones under condensation of lead atoms in cold He gas.…”
Section: ■ Introductionmentioning
confidence: 99%